Effect of high temperature environment on the performance of LiNi0.5Co0.2Mn0.3O2 battery. (January 2017) - Situ, Wenfu; Yang, Xiaoqing; Li, Xinxi; Zhang, Guoqing; Rao, Mumin; Wei, Chao; Huang, Zhi
Highlights: Thermal generation behavior of 18650 NCM523 batteries is investigated. The decreased thermal effect is ascribed to the increased internal resistance. The high environment temperature also leads to a capacity fading obviously. The crystal/nano structure of the cathode is destroyed at high temperature. Abstract: Thermal generation behavior of 18650 ternary LiNi0.5 Co0.2 Mn0.3 O2 batteries was tested at working environment of 30 and 50 °C, respectively. The experimental results showed that the surface temperature difference of the battery at high temperature of 50 °C and its corresponding heating rate were both higher than those at 30 °C owing to the increased internal resistance, which also led to a decrease of lithium storage capacity obviously. By characterizing the crystal/nano structure of the ternary cathode materials, these phenomena could be ascribed to the damage of the crystal structure and aggregation of the electrode materials.